Contradictory Effect of Lymphocyte Therapy and Prednisolone Therapy on CD3+CD8+CD56+ Natural Killer T Population in Women with Recurrent Spontaneous Abortion - Fatemeh Rezayat; Nafiseh Esmaeil; Abbas Rezaei; Roya Sherkat (Journal of Human Reproductive Sciences)
Background: Natural killer T (NKT) cells are influential immune cells in pregnancy failures, including recurrent spontaneous abortion (RSA). Different approaches are used for these disorders due to their effects on maternal immunomodulation. Aims: In the present study, we compared the effects of two typical immunotherapies (lymphocyte immunotherapy [LIT] and low-dose prednisolone) on CD3+CD56+CD16+ and CD3+CD56+CD8+ cells as two distinct subsets of NKT cells in Women with RSA. Settings and Design: This study was a comparative cohort study conducted from 2021 to 2022. One hundred and five women with RSA were distributed into three treatment groups randomly. Materials and Methods: Fifty women in the group of low-dose prednisolone therapy, fifty women in the LIT group and five women without any treatment as the control group were included in the study. NK and NKT cell subsets were assessed using flow cytometry. Furthermore, the concentration of interferon-gamma (IFN-γ), transforming growth factor-beta (TGF-β) and interleukin-10 (IL-10) was measured quantitatively using the enzyme-linked immunosorbent assay technique. Statistical Analysis Used: Normality and comparisons between study groups were performed by non-parametric unpaired Mann–Whitney, Kruskal–Wallis rank sum test, and one-way ANOVA. Results: The percentage of CD56dim NK cells was increased after prednisolone therapy, while this population significantly decreased in the LIT group. In contrast to the LIT group, the administration of prednisolone increased CD3+CD8+CD56+ NKT cells (P < 0.0001), which is helpful for pregnancy. The effect of the investigated treatment approaches on the population of peripheral CD3+CD56+CD16+ NKT cells of women with RSA was not adequately significant. The same situation was also observed regarding the serum level of IFN-γ. However, a significant decrease in serum levels of IL-10 and TGF-β was observed after prednisolone therapy. Conclusion: The lower capability of LIT in changing the population of NKT cells compared to prednisolone therapy may be due to its mechanism of action, which is related to the production of blocking antibodies. These treatment approaches had different effects on NKT cells, indicating that NKT cell population and function can be affected using LIT and prednisolone therapy distinctly. In addition, prednisolone therapy and LIT in women with normal serum levels of IFN-γ have no harmful effects in changing the production of this critical cytokine.